Casting Light on the Distinctive Contribution of Social Work in Multidisciplinary Teams for Older People. (4th February 2021) - Willis, Paul; Lloyd, Liz; Hammond, Jackie; Milne, Alisoun; Nelson-Becker, Holly; Perry, Emma; Ray, Mo; Richards, Sally; Tanner, Denise
Abstract: The current policy emphasis in adult social care in England is on promoting independence, preventing or delaying the need for more intensive support and the provision of personalised services. However, there is little evidence available on how social workers (SWs) identify and meet the complex needs of older service users in practice. In this article, we present findings from a study of innovative social work practice with older adults in England (2018–2019). We present five case studies of social care and integrated services in which SWs are integral team members. Twenty-one individuals participated in interviews; this included service managers and practitioners with social work backgrounds, and other professionals, including nurses and occupational therapists. Specific practices contributing to innovative service delivery included: the strong demonstration of social work values influencing the practice of multidisciplinary teams; positive risk management; importance of timing and ensuring continuity of relationships; and, the proactive application of legal knowledge to promote older people's rights. While some of these features can be seen as returning to the 'heart' of social work, we argue that they are promising in forging new paths for social work with older people that turn away from more managerialist- and procedurally driven approaches.